The Influence of Differentiated Learning on Motivation and Economic Learning Outcomes of Class XI Students at SMA Negeri 6 Surakarta - Rahmandhani, Fahriza; Noviani, Leny (Soedirman Economics Education Journal, 2024)
This research aims to determine the effect of implementing differentiated learning on the motivation and Economic learning outcomes of class XI students at SMA Negeri 6 Surakarta. This study is experimental research utilizing a Pretest-Posttest Control Group Design. The sampling technique used was purposive sampling and using class XI F-6 as the experimental class and XI F-10 as the control class. Data collection techniques were carried out using questionnaire instruments, pretest and posttest. Data analysis included assumption test such as normality and homogeneity tests before hypothesis testing is carried out using the independent sample T-test. The results show that (1) differentiated learning has a significant influence on the learning motivation as indicated by the acquisition of a significance value (Sig. 2 tailed) 0,001 < 0,05; (2) differentiated learning has a significant influence on the learning outcomes as evidenced by the acquisition of a significance value (Sig. 2 tailed) with an average posttest value of 0,000 < 0,05. This research can contribute to the development of education related to the topic of differentiated learning. In addition, this research provides novelty in improving the quality of Economic learning through adjusting learning method based on student’s interests, needs, and learning readiness to improve motivation and learning outcomes. Researchers hope that future research can be expanded by using other factors to improve the influence of differentiated learning on motivation and learning outcomes